استخدام المفردات الدينية واستغلال الألفاظ العربية المقترضة في اللغة الماليزية في إعداد نصوص المطالعة للطلبة الماليزيين بالمرحلة الثانوية: نموذج مقترح = The use of religious vocabulary and the exploitation of Arabic words borrowed in the Malaysian language in the preparation of reading text for Malaysian high school students: selected case study - Ismail, Yasir; Salleh, Radziah (Department of Usuluddin and Comparative Religion, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University of Malaysia, 2018)
This paper attempt to highlight the use of Arabic religious words in the Malay language. The authors stress on the issue of how these vocabularies of Arabic language were employed into the Malay language and used in the preparation of reading texts of Malaysian high school students. The authors employ the qualitative methodology by applying textual and content analysis on the selected cases of study that are related to the topic. Findings reveal that in order to assist the understanding of the Arabic language among young generation of the Malays, many Arabic vocabularies that were borrowed by the Malay language were employed in preparing the reading text for high school students of the religious stream of the Malaysian Educational system.